A A new species of Catasetum (Cymbidieae: Catasetinae) from the Colombian Amazonia - Calderón Álvarez, R. Alexis; Bonilla Morales, Miguel M. (Lankesteriana: International Journal on Orchidology, 2023)
A new species, Catasetum caquetense from the Caquetá department of the Colombian Amazonia, is described and illustrated. Catasetum caquetense is morphologically distinct from similar species such as C. tuberculatum in its rectangular, entire, denticulate, prominent apiculate basal callus surrounded by inconspicuous crown-shaped protrusions with an extra callus towards the apex that partially narrows towards the mid-lip. Information about its distribution, ecology, habitat, and taxonomic comments on morphologically similar species is also provided. With this addition, the genus comprises eight species in the department of Caquetá.